Marking and Making Differences: Representational Diversity in the U.S. Southwest. Issue 2 (April 2016) - Hegmon, Michelle; Freeman, Jacob; Kintigh, Keith W.; Nelson, Margaret C.; Oas, Sarah; Peeples, Matthew A.; Torvinen, Andrea
Abstract: Diversity is generally valued, although it sometimes contributes to difficult social situations, as is recognized in recent social science literature. Archaeology can provide insights into how diverse social situations play out over the long term. There are many kinds of diversities, and we propose representational diversity as a distinct category. Representational diversity specifically concerns how and whether differences are marked or masked materially. We investigate several archaeological sequences in the U.S. Southwest. Each began with the coming together of populations that created situations of unprecedented social diversity; some resulted in conflict, others in long-term stability. We trace how representational diversity changed through these sequences. Specifically, we review the transregional Kayenta migration to the southern Southwest and focus empirical analyses on regional processes in the Cibola region and on painted ceramics. Results show that, initially, representational diversity increased above and beyond that caused by the combination of previously separate traditions as people marked their differences. Subsequently, in some instances, the diversity was replaced by widespread homogeneity as the differences were masked and mitigated. Although the social causes and effects of diversity are many and varied, long-term stability and persistence is associated with tolerance of a range of diversities.